Genome sequences of six wheat-infecting fusarium species isolates - Moolhuijzen, Paula; Manners, J.; Wilcox, S.; Bellgard, M.; Gardiner, D. (2013)
Fusarium pathogens represent a major constraint to wheat and barley production worldwide. To facilitate future comparative studies of Fusarium species that are pathogenic to wheat, the genome sequences of four Fusarium pseudograminearum isolates, a single Fusarium acuminatum isolate, and an organism from the Fusarium incarnatum-F. equiseti species complex are reported.